A core-shell rare earth upconversion luminescent nanomaterial and its preparation method and application

By upconverting luminescent nanomaterials with core-shell shell structures, the problem of insufficient luminescence brightness and light stability of existing materials at the single-particle level is solved, and a single-particle imaging effect with high brightness and high signal-to-noise ratio is achieved.

CN115161009BActive Publication Date: 2025-03-14FUDAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210776028.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-02
Publication Date
2025-03-14
Estimated Expiration
2042-07-02

AI Technical Summary

Technical Problem

The existing rare earth up-converting luminescent materials have low luminescence brightness at the single particle level and insufficient light stability, which limits their application in single-molecular imaging.

Method used

Rare earth up-converting luminescent nanomaterials using core-shell shell structures are composed of NaYb1-x-yRExLnyF4@NaYbF4@NaREF4. This structure suppresses the surface quenching effect and improves the photon capture ability. Combined with an optimized preparation method, the brightness and light stability of the material are improved.

Benefits of technology

It is realized that visible light or near-infrared emission bands in the 300-850nm band are generated under laser excitation of 900-1000nm, which significantly improves the brightness of a single particle and obtains a higher signal-to-noise ratio. It is suitable for single particle imaging and motion tracking of cell membrane EGFR proteins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115161009B_ABST
    Figure CN115161009B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of luminescent materials, and specifically relates to a core-shell rare earth upconversion luminescent nanomaterial and its preparation method and application. The general formula of the upconversion luminescent nanomaterial of the present invention is: NaYb 1‑x‑y RE x Ln y F4@NaYbF4@NaREF4; RE is Gd, Y or Lu atom; Ln is Er, Tm or Ho atom; NaYbF4 is sensitizing layer; total particle size is 5nm-100nm. This material produces visible or near-infrared light emission band in the 300-850nm band under 900-1000nm laser excitation; nanoparticles with a particle size of about 10nm can emit visible or near-infrared light at an excitation light power density of 22kW cm ‑2 Under the excitation of 980nm laser, a single nanoparticle can emit 4300 photons per second; under the excitation of near-infrared light, it obtains strong upconversion luminescence and has a high signal-to-noise ratio; it can be used for single particle imaging: including single particle detection, super-resolution imaging based on single particle positioning and single particle tracking, such as the movement tracking of EGFR protein on the cell membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a core-shell upconversion luminescent nanomaterial and a preparation method and application thereof. Background Art

[0002] Single-molecule imaging has high positioning accuracy and tracking capabilities, and has become a powerful tool for studying the specificity of different individuals in a series of microscopic movements such as cell activities and molecular microscopic processes. Single-molecule tracking relies heavily on luminescent probes, commonly used fluorescent proteins and organic small molecule dyes. However, these luminescent probes are subject to certain limitations in tracking imaging due to their poor photostability and light blinking characteristics. Rare earth element-doped upconversion nanoparticles (UCNPs) have excellent photostability and no light blinking. In addition, due to their unique anti-Stokes shift luminescence process, they can eliminate the interference of biological sample autofluorescence and achieve low background imaging, making them a good single particle imaging labeling probe. However, due to the weak light absorption ability of rare earth ions and the influence of factors such as surface quenching and non-radiative dissipation, the luminescence brightness of this type of material at the single particle level needs to be improved.

[0003] In order to improve the luminescence brightness of rare earth upconversion luminescent materials, protection with inert shells can inhibit surface quenching and increase brightness, but this will inevitably increase the particle size of the nanomaterial, which will affect the movement of the labeled object during tracking. The upconversion luminescence can be enhanced by improving the photon capture ability or energy transfer efficiency through organic small molecule coordination. However, due to the poor chemical stability and photostability of organic ligands, this type of method is still not suitable for single particle imaging. However, the relatively high irradiation power can cause damage to biological samples and is not suitable for single molecule tracking. Therefore, designing UCNPs with high brightness and excellent photostability for single molecule tracking remains a key challenge. Summary of the invention

[0004] The purpose of the present invention is to provide a rare earth up-conversion luminescent nanomaterial with high brightness and high photostability and suitable for single particle imaging.

[0005] The rare earth upconversion luminescent nanomaterial provided by the present invention is a photoluminescent core-shell structure nanomaterial, which comprises a first core layer of NaYb 1-xy RE x Ln y F4, the second layer NaYbF4, the third layer NaREF4, a total of 3 layers, the structure is written as the general formula: NaYb 1-x-y RE x Ln yF4@NaYbF4@NaREF4; in the first layer, RE is Gd, Y or Lu atom, x=0~0.70, Ln is Er, Tm or Ho atom, y is 0.01~1.00, x+y is not greater than 1.00; in the third layer, RE is Gd, Y or Lu atom; the second layer NaYbF4 is the sensitizing layer.

[0006] Preferably, the material structural formula is NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4 or

[0007] NeA 0.92 Er 0.08 F4@NaYbF4@NaLuF4.

[0008] The rare earth up-conversion luminescent nanomaterial provided by the present invention has a total particle size of 5nm to 100nm.

[0009] The present invention also provides a method for preparing the rare earth up-conversion luminescent nanomaterial, the specific steps of which are as follows:

[0010] (1) taking a rare earth chloride (ErCl3.6H2O, YbCl3.6H2O, LuCl3.6H2O or GdCl3.6H2O) and dissolving it in an oleic acid (OA) solvent at 80-150°C, and evaporating the water in an open manner to prepare a uniform and transparent rare earth oleate solution such as Er(OA)3, Yb(OA)3, Lu(OA)3, or Gd(OA)3;

[0011] (2) taking the oleates of Re, Yb and Er corresponding to the core rare earth fluoride nanoparticles, adding sodium oleate and ammonium fluoride, and dissolving them in a solvent at 100-150°C;

[0012] (3) The reaction solution obtained in step (2) is heated to 270-330° C. under nitrogen protection and maintained for 15 min-1 h, and then cooled to room temperature;

[0013] (4) adding ethanol to the reaction solution obtained in step (3), obtaining a solid after centrifugal separation, and washing the solid with a mixed solution of cyclohexane and ethanol;

[0014] (5) Preparation of the second sensitizing layer: Take the Yb(OA)3 solution prepared in step (1), add sodium hydroxide, ammonium fluoride and a solvent, stir at 80-100°C to form a uniform solution, and evaporate part of the water and low-boiling point compounds in an open state;

[0015] (6) adding the solid obtained in step (3) to the solution prepared in step (5) and mixing them uniformly; then heating the mixture to 270-330° C. under nitrogen protection, maintaining the temperature for 15 min-1 h, and then cooling the mixture to room temperature;

[0016] (7) adding ethanol to the reaction solution obtained in step (6), obtaining a solid after centrifugal separation, and washing the solid with a mixed solution of cyclohexane and ethanol;

[0017] (8) taking the rare earth oleic acid solution required for preparing the third layer, adding sodium hydroxide, ammonium fluoride and a solvent, stirring at 80-100° C. to form a uniform solution, and evaporating part of the water and low-boiling point compounds in an open state;

[0018] (9) adding the solid obtained in step (7) to the solution prepared in step (8) and mixing well; then heating to 270-330° C. under nitrogen protection, maintaining for 15 min-1 h, and then cooling to room temperature;

[0019] (10) adding ethanol to the reaction solution obtained in step (9), centrifuging to obtain a solid, and washing it with a mixed solution of cyclohexane and ethanol; dispersing the prepared solid in cyclohexane to obtain a rare earth up-conversion nanomaterial with a size of less than 10 nanometers.

[0020] Preferably, in step (1), step (2), step (5) and step (8), the solvent is at least one of oleic acid and octadecene.

[0021] Preferably, in step (1), step (5) and step (8), the open water removal time is 30 to 60 minutes.

[0022] Preferably, in step (3), step (6) and step (9), the temperature of the high temperature reaction is 290-305°C.

[0023] Preferably, in step (4), step (7) and step (10), the centrifugal separation is carried out at a speed of 8000-16500 rpm for 5-20 minutes, and the solid separated by centrifugation is washed with a mixture of cyclohexane and ethanol.

[0024] Preferably, in step (4), step (7) and step (10), the volume ratio of ethanol to cyclohexane in the mixed solution of ethanol and cyclohexane is 1:1 to 5:1, and the number of washing times is 2 to 3 times.

[0025] The ultra-bright rare earth up-conversion luminescent nanomaterial constructed by the present invention generates visible light or near-infrared emission bands in the 300-850nm band under 900-1000nm laser excitation. The power density is 10W / cm 2 ~10MW / cm 2The nanoparticles with a particle size of about 10 nm were excited by a light power density of 22 kW cm -2 Under the excitation of 980nm laser, the single particle brightness can reach 4300 photons per second. The remarkable feature of this kind of material is that it can obtain strong upconversion luminescence under near-infrared light excitation and obtain a high signal-to-noise ratio.

[0026] Based on the above characteristics, the rare earth upconversion luminescent nanomaterials of the present invention can be used for single particle imaging, and the specific power density can be 10W / cm 2 ~10MW / cm 2 , with a wavelength of 900-1000nm laser excitation irradiation; the single particle imaging includes: single particle tracing, single particle detection, and super-resolution imaging based on single particle positioning.

[0027] Furthermore, the rare earth up-conversion luminescent nanomaterial of the present invention can also be used for tracking the movement of cell membrane EGFR protein.

[0028] The application of the rare earth upconversion luminescent nanomaterial provided by the present invention in single particle imaging comprises the following specific steps:

[0029] (1) Preparation of single-particle nanoparticle samples: adsorb rare earth upconversion luminescent nanomaterials (solid nanoparticles) with a particle size of less than 10 nanometers on a cover glass; drop polylysine on the cover glass, and then ultrasonically disperse the solid material in cyclohexane to dilute the concentration to 10 -5 ~10 -6 mg / mL; the diluted material was dropped onto the coverslip;

[0030] (2) laser excitation of a single particle sample; the single particle nanoparticle sample prepared in step (1) is placed on an optical microscope stage and excited with a 980 nm laser, and the emission light of the sample is received by an EMCCD camera connected to the microscope through the objective lens;

[0031] (3) Measurement of the luminescence properties of single-particle samples; fitting the point spread function of each particle in the data collected by the EMCCD camera with a two-dimensional Gaussian function; then removing the background term from the fitted Gaussian function and using the integral over the entire plane to represent the luminescence intensity of each particle; discarding the point spread function that cannot be fitted or has a small fitting correlation coefficient.

[0032] The application of the rare earth upconversion nanomaterial provided by the present invention in the movement tracking of cell membrane EGFR protein comprises the following specific steps:

[0033] (1) PAA modification of single-particle nanoparticles: Rare earth upconversion nanomaterials (solid nanoparticles) with a size of less than 10 nanometers are dispersed in a chloroform solution of NOBF4, the surface ligands are removed, polyacrylic acid (PAA) is added, and after ultrasonic dispersion, stirring is performed for 10-24 hours, and centrifugation is performed to obtain PAA-modified nanoparticles;

[0034] (2) PEG modification of nanoparticles: the nanoparticles obtained in step (1) are dispersed in DMF, EDC and NHS are added and stirred for 1 to 2 hours, and then NH2-PEG-COOH is added and stirred for 4 to 12 hours, and centrifuged to obtain PEG-modified nanoparticles;

[0035] (3) Anti-EGFR modification of nanoparticles: the nanoparticles obtained in step (2) are dispersed in water, EDC and NHS are added and stirred for 1 to 2 hours, then anti-EGFR is added and stirred for 0.8 to 11.5 hours, and centrifuged to obtain anti-EGFR modified nanoparticles, which are dispersed in water;

[0036] (4) Incubating cells with nanoparticles: adding the nanoparticle aqueous solution obtained in step (3) to the cell culture medium, incubating with the cells for 10-60 min, discarding the supernatant, and washing with blank culture medium three times to remove the free nanoparticles on the surface;

[0037] (5) Laser excitation of nanoparticle samples; single-particle tracking of EGFR on the cell membrane, placing the cell sample labeled with anti-EGFR modified nanoparticles on the stage of a scientific research optical microscope, exciting the sample with a 980 nm laser, and the emission light signal of the sample is received by an EMCCD camera connected to the microscope;

[0038] (6) Tracking the movement of cell membrane EGFR protein: Analyze the data collected by the EMCCD camera, first use the MATLAB program to find the position of each located particle and its trajectory over time, and calculate the MSD (mean square displacement) of each trajectory over time. Then, according to the Brownian motion model, an exponential function is fitted to the relationship between each MSD and time to determine the diffusion coefficient and other parameters of the EGFR located by each particle; the single particle positioning accuracy is calculated according to the Thompson formula. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a transmission electron microscope photo of Example 1. Among them, the three sub-pictures are:

[0040] NeA 0.92 Er 0.08 F4,NaYb 0.92 Er 0.08F4@NaYbF4 and NaYb 0.92 Er 0.08 Transmission electron microscopy image of F4@NaYbF4@NaLuF4 rare earth nanoparticles; the particle sizes are 10, 13 and 14 nm respectively.

[0041] Figure 2 It is a transmission electron microscope photo of Example 2. Among them, the three sub-images are: NaYb 0.82 G 0.1 Er 0.08 F4,NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4 and NaYb 0.82 G 0.1 Er 0.08 Transmission electron micrograph of F4@NaYbF4@NaLuF4 rare earth nanoparticles, with particle sizes of 6.9, 8.8 and 9.9 nm respectively.

[0042] Figure 3 This is the up-conversion luminescence spectrum of Example 3. Including: NaYb 0.92 Er 0.08 F4,NaYb 0.92 Er 0.08 F4@NaYbF4 and NaYb 0.92 Er 0.08 F4@NaYbF4@NaLuF4.

[0043] Figure 4 This is the up-conversion luminescence spectrum of Example 4. Including: NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4 and NaYb 0.82 G 0.1 Er 0.08 Upconversion emission spectra of F4@NaYbF4@NaLuF4 rare earth nanoparticles.

[0044] Figure 5 is NaYb in Example 5 0.82 G 0.1 Er 0.08 Scanning electron microscope image of F4@NaYbF4@NaLuF4 and single particle imaging under wide-field microscope.

[0045] Figure 6 The intensity power curve and the luminous intensity divided by particle volume bar graph of Example 5. Wherein, (a) is NaYb 0.82 G 0.1 Er 0.08F4@NaYbF4@NaLuF4,NaYb 0.82 G 0.1 Er 0.08 F4@NaLuF4,NaYF4@NaY 0.72 Yb 0.2 Er 0.08 F4,NaYb 0.82 G 0.1 Er 0.08 F4@NaYb 0.92 Er 0.08 F4@NaLuF4,NaYF4:20%Yb,20%Er@NaLuF4 and NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4 nanoparticles, at a power density of 680 W cm -2 Up to 21.7kW cm -2 Single particle upconversion luminescence intensity curve within the power range. (b) According to Figure (a), at a power density of 2.8 kW cm -2 The upconversion luminescence intensity bar graph of the nanoparticles per unit volume is obtained by comparing the single particle luminescence intensity with the corresponding particle volume.

[0046] Figure 7 This is a single particle imaging image of cell EGFR tracking in Example 6. Specifically, the movement trajectory of EGFR protein in U2OS cells tracked by UCNPs-PEG-antiEGFR labeling and the positioning accuracy obtained by Gaussian fitting of the PSF of UCNP. DETAILED DESCRIPTION

[0047] In order to make the present invention more clearly understood, preferred embodiments are provided for further explanation in conjunction with the accompanying drawings.

[0048] Example 1

[0049] NaYb with a particle size of 14 nm 0.92 Er 0.08 Synthesis of F4@NaYbF4@NaLuF4:

[0050] 10 mmol of rare earth chloride (YbCl3.6H2O, ErCl3.6H2O or LuCl3.6H2O) was mixed with 10 mL of oleic acid (OA) and 10 mL of octadecene (ODE) in a 100 mL three-necked flask, and the solution was heated to 150 °C and maintained for 60 min to obtain a transparent solution to obtain ytterbium oleate, erbium oleate and lutetium oleate solutions, which were then cooled to room temperature for use.

[0051] 0.92 mL of ytterbium oleate solution and 0.08 mL of erbium oleate solution were placed in a three-necked flask, 15 mL of ODE and 6 mL of OA were added, 2.03 g of sodium oleate and 1.484 g of ammonium fluoride were added, and then heated to 120 ° C under nitrogen blowing, maintained for 50 min, and then vacuumed for 10 min. Under nitrogen protection, the system was heated to 290 ° C, maintained for 50 min, and then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugal separation, and then the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v).

[0052] The above solid was dispersed in a mixed solution of 10 mL OA and 10 mL LODE, 0.5 mL ytterbium oleate solution was added, heated to 120 ° C and maintained for 30 min to obtain a transparent solution, then cooled to 50 ° C, and NH4F (1.7 mmol) and NaOH (1.25 mmol) dissolved in 10 mL methanol were added to the solution after cooling to room temperature, and then degassed at 90 ° C for 30 minutes to remove methanol. Under the protection of nitrogen, the system was heated to 300 ° C, maintained for 0.5 hours, and then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugal separation, and then the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v).

[0053] The above solid was dispersed in a mixed solution of 10 mL OA and 10 mL ODE, 0.5 mL ytterbium oleate solution was added, heated to 120 ° C and maintained for 30 min to obtain a transparent solution, then cooled to 50 ° C, and after cooling to room temperature, NH4F (1.7 mmol) and NaOH (1.25 mmol) dissolved in 10 mL methanol were added to the solution, followed by degassing at 90 ° C for 30 minutes to remove methanol. Under nitrogen protection, the system was heated to 300 ° C, maintained for 0.5 hours, and then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugal separation, and then the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v).

[0054] The above solid was dispersed in a mixed solution of 10 mL OA and 10 mL ODE, 0.5 mL lutetium oleate solution was added, heated to 120 ° C and maintained for 30 min to obtain a transparent solution, then cooled to 50 ° C, and after cooling to room temperature, NH4F (1.7 mmol) and NaOH (1.25 mmol) dissolved in 10 mL methanol were added to the solution, followed by degassing at 90 ° C for 30 minutes to remove methanol. Under nitrogen protection, the system was heated to 300 ° C and maintained for 0.5 hours, then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugation, and then the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v). The synthesized NaYb0.92 Er 0.08 F4@NaYbF4@NaLuF4 has uniform morphology and a particle size of about 14nm ( Figure 1 ).

[0055] Example 2

[0056] NaYb with a particle size of 9.9 nm 0.82 G 0.1 Er 0.08 Synthesis of F4@NaYbF4@NaLuF4:

[0057] Take 0.82mL of ytterbium oleate solution and 0.08mL of erbium oleate solution in a three-necked bottle, add 0.1mmol GdCl3.6H2O, add 15mL ODE and 6mL OA, add 2.03g sodium oleate and 1.484g ammonium fluoride, then heat to 120℃ under nitrogen blowing, keep for 50min, and then evacuate for 10min. Under nitrogen protection, the system is heated to 300℃, kept for 30min, and then cooled to room temperature, and the same volume of ethanol is added to the cooled solution, and the solid is obtained by centrifugal separation, and then the obtained solid is washed three times with a solution of ethanol: cyclohexane (1:1v / v).

[0058] The above solid was dispersed in a mixed solution of 10 mL OA and 10 mL ODE, 0.3 mL ytterbium oleate solution was added, heated to 120 ° C and maintained for 30 min to obtain a transparent solution, then cooled to 50 ° C, and after cooling to room temperature, NH4F (1.2 mmol) and NaOH (0.75 mmol) dissolved in 10 mL methanol were added to the solution, followed by degassing at 90 ° C for 30 minutes to remove methanol. Under nitrogen protection, the system was heated to 300 ° C, maintained for 0.5 hours, and then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugal separation, and then the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v).

[0059] The above solid was dispersed in a mixed solution of 10 mL OA and 10 mL ODE, 0.2 mL ytterbium oleate solution was added, heated to 120 ° C and maintained for 30 min to obtain a transparent solution, then cooled to 50 ° C, and NH4F (0.34 mmol) and NaOH (0.25 mmol) dissolved in 10 mL methanol were added to the solution after cooling to room temperature, and then degassed at 90 ° C for 30 minutes to remove methanol. Under the protection of nitrogen, the system was heated to 300 ° C and maintained for 0.5 hours, and then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugal separation, and the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v).

[0060] The above solid was dispersed in a mixed solution of 10 mL OA and 10 mL ODE, 0.2 mL lutetium oleate solution was added, heated to 120 ° C and maintained for 30 min to obtain a transparent solution, then cooled to 50 ° C, and after cooling to room temperature, NH4F (0.34 mmol) and NaOH (0.25 mmol) dissolved in 10 mL methanol were added to the solution, followed by degassing at 90 ° C for 30 minutes to remove methanol. Under nitrogen protection, the system was heated to 300 ° C and maintained for 0.5 hours, then cooled to room temperature, and the same volume of ethanol was added to the cooled solution, and the solid was obtained by centrifugation, and then the obtained solid was washed three times with a solution of ethanol: cyclohexane (1:1 v / v). The synthesized NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4 has uniform morphology and a particle size of about 9.9nm ( Figure 2 ).

[0061] Example 3

[0062] NeA 0.92 Er 0.08 F4、NaYb 0.92 Er 0.08 F4@NaYbF4 and NaYb 0.92 Er 0.08 Comparison of upconversion spectrum intensity of F4@NaYbF4@NaLuF4:

[0063] NaYb 0.92 Er 0.08 F4、NaYb 0.92 Er 0.08 F4@NaYbF4@ and NaYb 0.92 Er 0.08 F4@NaYbF4@NaLuF4 was dispersed in cyclohexane to prepare a 10 mg / mL solution. 1 mL was taken into a quartz cuvette and a 980 nm laser was used as the excitation light source to obtain NaYb 0.92 Er 0.08 F4、NaYb 0.92 Er 0.08 F4@NaYbF4@ and NaYb 0.92 Er 0.08 Upconversion spectrum of F4@NaYbF4@NaLuF4 ( Figure 3 ).

[0064] Example 4

[0065] NeA 0.82 G 0.1 Er 0.08 F4、NaYb0.82 G 0.1 Er 0.08 F4@NaYbF4 and NaYb 0.82 G 0.1 Er 0.08 Comparison of upconversion spectrum intensity of F4@NaYbF4@NaLuF4: Na Yb 0.82 G 0.1 Er 0.08 F4、Na Yb 0.82 G 0.1 Er 0.08 F4@NaYbF4@ and NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4 was dispersed in cyclohexane to prepare a 10 mg / mL solution. 1 mL was taken into a quartz cuvette and a 980 nm laser was used as the excitation light source to obtain Na Yb 0.82 G 0.1 Er 0.08 F4、NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4@ and NaYb 0.82 G 0.1 Er 0.08 Upconversion spectrum of F4@NaYbF4@NaLuF4 ( Figure 4 ).

[0066] Example 5

[0067] NeA 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4、NaYb 0.82 G 0.1 Er 0.08 F4@NaLuF4,

[0068] NaYF4@NaY 0.72 Yb 0.2 Er 0.08 F4、NaYb 0.82 G 0.1 Er 0.08 F4@NaYb 0.92 Er 0.08 F4@NaLuF4,

[0069] NaYF4:20%Yb,20%Er@NaLuF4 and NaYb 0.82 G 0.1 Er 0.08Wide-field microscopy single particle imaging of F4@NaYbF4:

[0070] 100 μL of polylysine aqueous solution was dripped on the coverslips, and then rinsed with cyclohexane 5 times after 1 min and dried. 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4、NaYb 0.82 G 0.1 Er 0.08 F4@NaLuF4,

[0071] NaYF4@NaY 0.72 Yb 0.2 Er 0.08 F4、NaYb 0.82 G 0.1 Er 0.08 F4@NaYb 0.92 Er 0.08 F4@NaLuF4,

[0072] NaYF4:20%Yb,20%Er@NaLuF4 and NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4 cyclohexane solution (~10 -4 mg / mL). After standing for 1 min, rinse with cyclohexane and air dry.

[0073] The prepared single-particle nanoparticle sample was placed on the stage of an optical microscope for scientific research, and the sample was excited by a 980nm laser through an objective lens (100×, NA1.49). The emission light of the sample passed through the objective lens and then passed through a 750nm low-pass emission filter to filter the excitation light, and then was received by the EMCCD camera connected to the microscope. Data of about 10 fields of view were collected for each sample at the same power.

[0074] Then, a two-dimensional Gaussian fit is performed on the point spread function I(x,y) of each particle in the collected data:

[0075]

[0076] where θ is the tilt angle, x0 and y0 are the center positions of the point spread function, and σ x and σ yis the standard deviation in the x and y directions, I0 is the total number of photons emitted by the particle, and C is the background. Point spread functions that cannot be fitted or have a small fitting correlation coefficient are not included in the statistics. The luminous intensity of each particle is defined as the number of photons emitted per unit time, that is, the integral of the fitting function minus the background on the entire plane divided by the exposure time:

[0077]

[0078] Where τ is the exposure time of the EMCCD camera. For each sample, the luminous intensity of hundreds of single particles is counted at each power density, and the average value is taken as the luminous intensity of the sample. The standard deviation of the luminous intensity is divided by the square root of the number of particles counted as the error of the luminous intensity at that power ( Figure 5 and Figure 6 )

[0079] Example 6

[0080] NeA 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4-PEG-antiEGFR is used for EGFR protein tracking in cells:

[0081] 10 mg of synthesized NaYb0.82Gd0.1Er0.08F4@NaYbF4@NaLuF4 nanoparticles were dispersed in 2 mL of NOBF4 chloroform solution to remove surface ligands, and centrifuged at 16500 rpm for 15 min. The supernatant was discarded, the precipitate was dispersed in 5 mL of DMF, 30 mg of polyacrylic acid (PAA) was added, and after ultrasonic dispersion, it was stirred for 12 h, and centrifuged at 16500 rpm for 15 min to obtain PAA-modified nanoparticles.

[0082] The solid was dispersed in 5 mL of DMF, EDC (10 mg) and NHS (10 mg) were added and stirred for 2 h, then 20 mg of NH2-PEG-COOH was added and stirred for 6 h, and the mixture was centrifuged at 16500 rpm for 15 min to obtain PEG-modified nanoparticles.

[0083] The solid was dispersed in 5 mL of DMF, EDC (10 mg) and NHS (10 mg) were added and stirred for 2 h, and then centrifuged at 16500 rpm for 15 min. The solid was dispersed and added to 10 μL of anti-EGFR antibody solution (1 mg / mL), stirred for 1 h, and centrifuged at 16500 rpm for 15 min to obtain anti-EGFR modified nanoparticles, which were dispersed in 1 mL of water.

[0084] 10 μL of anti-EGFR modified nanoparticle aqueous solution was added to the cell culture medium and incubated with the cells for 30 min. The supernatant was discarded and the cells were washed three times with blank culture medium to remove the free nanoparticles on the surface.

[0085] Place the cell sample labeled with anti-EGFR modified nanoparticles on the stage of a scientific optical microscope, first find cells of appropriate size under bright field, and then -2 The sample was excited with a 980nm laser at an excitation light power density of 100 nm. The emission light of the sample was received by an EMCCD camera connected to a microscope through a 750nm low-pass emission filter, thereby recording the movement of EGFR labeled with nanoparticles. The data acquisition time was 30-60 minutes.

[0086] Analyze the collected data, first use the MATLAB program to find the position of each located particle and the trajectory of each particle over time. Calculate the change of MSD (mean square displacement) of each trajectory over time, and then fit the relationship between each MSD and time according to the Brownian motion model to determine the diffusion coefficient and other parameters of the EGFR located by each particle:

[0087] MSD=4Dt α +offset

[0088] Where D is the diffusion coefficient, α is the fitting parameter used to describe the motion pattern, and offset is the origin offset.

[0089] Each point spread function of each frame image is fitted, and the positioning accuracy of each single particle in each frame image is calculated according to the Thompson formula ( Figure 7 ):

[0090]

[0091] where s is the standard deviation of the point spread function, a is the pixel size of the camera, N is the number of photons, and b is the camera background noise.

Claims

1. A rare earth upconversion luminescent nanomaterial, characterized in that: It is a photoluminescent core-shell nanomaterial, which includes a first core layer of NaYb 1-xy RE x Ln y F4, the second layer NaYbF4, the third layer NaREF4, a total of 3 layers, the structure is written as the general formula: NaYb 1-x-y RE x Ln y F4@NaYbF4@NaREF4; in the first layer, RE is Gd, Y or Lu atom, x=0~0.70; Ln is Er, Tm or Ho atom, y is 0.01~1.00, x+y is not greater than 1.00; in the third layer, RE is Gd, Y or Lu atom; the second layer NaYbF4 is the sensitizing layer; the particle size is 5 nm ~ 100 nm.

2. The rare earth upconversion luminescent nanomaterial according to claim 1, characterized in that: The material structure is NaYb 0.82 G 0.1 Er 0.08 F4@NaYbF4@NaLuF4 or NaYb 0.92 Er 0.08 F4@NaYbF4@NaLuF4.

3. A method for preparing the rare earth up-conversion luminescent nanomaterial according to claim 1, characterized in that: The specific steps are as follows: (1) taking rare earth chloride ErCl3·6H2O, YbCl3·6H2O, LuCl3·6H2O or GdCl3·6H2O, dissolving it in oleic acid (OA) solvent at 80-150°C, and evaporating the water in an open state to prepare a uniform and transparent Er(OA)3, Yb(OA)3, Lu(OA)3, or Gd(OA)3 rare earth oleate solution; (2) Take the oleates of Re, Yb and Er corresponding to the core rare earth fluoride nanoparticles, add sodium oleate and ammonium fluoride, and dissolve them in a solvent at 100-150 °C; (3) The reaction solution obtained in step (2) is heated to 270-330°C under nitrogen protection and maintained for 15 min-1 h, and then cooled to room temperature; (4) adding ethanol to the reaction solution obtained in step (3), obtaining a solid after centrifugal separation, and washing the solid with a mixed solution of cyclohexane and ethanol; (5) Preparation of the second sensitizing layer: Take the Yb(OA)3 solution prepared in step (1), add sodium hydroxide, ammonium fluoride and a solvent, stir at 80-100°C to form a uniform solution, and evaporate part of the water and low-boiling point compounds in an open state; (6) adding the solid obtained in step (3) to the solution prepared in step (5) and mixing them evenly; then heating to 270-330° C. under nitrogen protection, maintaining the temperature for 15 min-1 h, and then cooling to room temperature; (7) adding ethanol to the reaction solution obtained in step (6), obtaining a solid after centrifugal separation, and washing the solid with a mixed solution of cyclohexane and ethanol; (8) Take the rare earth oleic acid solution required for preparing the third layer, add sodium hydroxide, ammonium fluoride and solvent, stir at 80-100° C. to form a uniform solution, and evaporate part of the water and low-boiling point compounds in an open air; (9) adding the solid obtained in step (7) to the solution prepared in step (8) and mixing them evenly; then heating to 270-330° C. under nitrogen protection, maintaining the temperature for 15 min-1 h, and then cooling to room temperature; (10) Add ethanol to the reaction solution obtained in step (9), centrifuge to obtain a solid, and wash it with a mixed solution of cyclohexane and ethanol; the prepared solid is dispersed in cyclohexane to obtain a rare earth upconversion luminescent nanomaterial with a size of less than 10 nanometers.

4. The method for preparing the rare earth up-conversion luminescent nanomaterial according to claim 3, characterized in that: In step (1), step (2), step (5) and step (8), the solvent is at least one of oleic acid and octadecene.

5. The method for preparing the rare earth up-conversion luminescent nanomaterial according to claim 3, characterized in that: In step (1), step (5) and step (8), the open water removal time is 30 to 60 minutes.

6. The method for preparing the rare earth up-conversion luminescent nanomaterial according to claim 3, characterized in that: In step (4), step (7) and step (10), the centrifugal separation is carried out at a speed of 8000-16500 rpm for 5-20 minutes.

7. The method for preparing the rare earth up-conversion luminescent nanomaterial according to claim 3, characterized in that: In step (4), step (7) and step (10), the volume ratio of ethanol to cyclohexane in the mixed solution of ethanol and cyclohexane is 1:1 to 5:1, and the number of washing times is 2 to 3 times.

8. Use of the rare earth upconversion luminescent nanomaterial as claimed in claim 1 or 2 in single particle imaging, or in tracking the movement of cell membrane EGFR protein; using a power density of 10 W / cm 2 ~10MW / cm 2 , near-infrared light source with a wavelength of 900-1000nm for excitation and irradiation; single particle imaging includes: Single particle tracking, single particle detection, and super-resolution imaging based on single particle localization.

9. The use according to claim 8, characterized in that: The application of the rare earth upconversion luminescent nanomaterial in single particle imaging comprises the following specific steps: (1) Preparation of single-particle nanoparticle samples: adsorb rare earth upconversion luminescent nanomaterials with a particle size of less than 10 nanometers on a cover glass; drop polylysine on the cover glass, and then ultrasonically disperse the solid material in cyclohexane to dilute the concentration to 10 -5 ~10 -6 mg / mL; the diluted material was dropped onto the coverslip; (2) laser excitation of a single-particle sample; the single-particle nanoparticle sample prepared in step (1) is placed on the stage of an optical microscope and excited with a 980 nm laser. The emission light of the sample is received by an EMCCD camera connected to the microscope through the objective lens; (3) Measurement of the luminescence properties of single-particle samples; the point spread function of each particle in the data collected by the EMCCD camera is fitted with a two-dimensional Gaussian function; the background term is then removed from the fitted Gaussian function, and the luminescence intensity of each particle is expressed by the integral over the entire plane; the point spread function that cannot be fitted is discarded.

10. The use according to claim 8, characterized in that: The application of the rare earth upconversion luminescent nanomaterial in the movement tracking of cell membrane EGFR protein comprises the following specific steps: (1) PAA modification of single-particle nanoparticles: rare earth upconversion luminescent nanomaterials with a size of less than 10 nanometers are dispersed in a chloroform solution of NOBF4, the surface ligands are removed, PAA is added, and after ultrasonic dispersion, the mixture is stirred for 10-24 hours, and the PAA-modified nanoparticles are obtained by centrifugation. (2) PEG modification of nanoparticles: the nanoparticles obtained in step (1) are dispersed in DMF, EDC and NHS are added and stirred for 1 to 2 h, then NH2-PEG-COOH is added, stirred for 4 to 12 h, and centrifuged to obtain PEG-modified nanoparticles; (3) Anti-EGFR modification of nanoparticles: the nanoparticles obtained in step (2) are dispersed in water, EDC and NHS are added and stirred for 1 to 2 hours, then anti-EGFR is added and stirred for 0.8 to 11.5 hours, and the mixture is centrifuged to obtain anti-EGFR modified nanoparticles, which are dispersed in water; (4) Incubating cells with nanoparticles: adding the nanoparticle aqueous solution obtained in step (3) to the cell culture medium, incubating with the cells for 10-60 min, discarding the supernatant, and washing with blank culture medium three times to remove the free nanoparticles on the surface; (5) Laser excitation of nanoparticle samples; single-particle tracking of EGFR on the cell membrane. The cell sample labeled with anti-EGFR-modified nanoparticles is placed on the stage of a scientific research optical microscope. The sample is excited with a 980nm laser. The emission light signal of the sample is received by an EMCCD camera connected to the microscope. (6) Tracking the movement of cell membrane EGFR protein: Analyze the data collected by the EMCCD camera, first use the MATLAB program to find the position of each located particle and its trajectory over time, and calculate the MSD of each trajectory over time. Then, according to the Brownian motion model, perform an exponential function fitting on the relationship between each MSD and time to determine the diffusion coefficient of the EGFR located by each particle. The single particle positioning accuracy is calculated according to the Thompson formula.

Citation Information

Patent Citations

  • Single-emission up-conversion nano fluorescent probe and synthetic method thereof

    CN104804741A

  • Near-infrared second window emission down-conversion nanometer fluorescence probe and synthesis method thereof

    CN107828408A